Comparing the Effect of Cimifugol and Salvigol on Night Sweats in Postmenopausal Women: A Single-blind Clinical Trial - Arezoo Shayan; Seyedeh Zahra Masoumi; Farzaneh Soltani; Roya Ahmadi Nia Tabesh; Shirin Morakhani; Maryam Farhadian; Reyhaneh Ebrahimi (Mashhad University of Medical Sciences, 2020)
Background & aim: Hot flashes and night sweats are the most common consequences of menopause. This study aimed to compare the effects of Cimifugol and Salvigol capsules on night sweat in postmenopausal women. Methods: This randomized clinical trial was carried out on 80 postmenopausal women who were assigned to two groups of Cimifugol (n=40) and Salvigol (n=40). The participants of each group were requested to take Cimifugol (6.5 mg) and Salvigol (100 mg) three times a day for two months. Wiklund vasomotor symptom scale was used to record the intensity and frequency of night sweats. The two groups completed this questionnaire before the intervention and then every week until the end of the intervention period (8 weeks). The data were analyzed in SPSS software (version 20) using through independent t-test, Chi-square, analysis of covariance, repeated measure ANOVA and repeated measure ANCOVA tests. Results: The mean±SD values of the number of sweats as well as its duration in the Salvigol group were 8.93±6.350 and 6.15±4.394 before the intervention, respectively. However, the corresponding values were 2.53±1.132 and 195±1.108, respectively after the intervention (at the end of the eighth week). Salvigol reduced the frequency of night sweats in different weeks (p <0.001). No significant difference was observed before and after the intervention in the Cimifugol group regarding the frequency and duration of night sweat (P>0.05). Conclusion: Based on the results, it is recommended to use Salvigol in the treatment of menopausal sweating.